Implementation of ECMPOs and disputes for control of the territory: the case of the ECMPO Mañihueico-Huinay and the mitiliculturists of Hualaihué, Region of Los Lagos (Revista LIDER, 2021)
This work analyzes the speeches and approaches of the Huilliche people and the musselfarmers in the face of the transformations of their coastal spaces due to the implementation of the Lafkenche Law in the Hualaihué commune. To carry out this research, a qualitative methodology was used with a review of secondary sources through a Critical Discourse Analysis (ACD). Among the results, a description of the arguments developed by two central actors in this process is presented: the Huilliche communities of Hualaihué, and the mussel farmers associated with seed collection. These actors articulate speeches in the face of the feeling of threat to their legitimate interests, identifying in turn the possible transformations on the coastline. The results show the different interests and meanings associated with the use of the coastline, through the establishment of unequal power relations fostered by an official policy that promotes extractive economic development, based on the protection of the aquaculture sector to the detriment of a culture that protects the natural resources and sustainability